Pregunta
What is \( (f+g)(x) \) ? \[ \begin{array}{l}f(x)=-2 x^{2}-6 x \\ g(x)=-x \\ \text { Write your answer as a polynomial or a rational function in simplest form. }\end{array} \]
Ask by Little Barrett. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( (f + g)(x) = -2x^2 - 7x \)
Solución
To find \( (f + g)(x) \), you simply add the functions \( f(x) \) and \( g(x) \) together.
Given:
\[
f(x) = -2x^2 - 6x
\]
\[
g(x) = -x
\]
Adding them:
\[
(f + g)(x) = (-2x^2 - 6x) + (-x) = -2x^2 - 7x
\]
So, the sum of the functions is:
\[
(f + g)(x) = -2x^2 - 7x
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Extra Insights
To find \( (f+g)(x) \), we simply add the given functions \( f(x) \) and \( g(x) \): \[ f(x) + g(x) = (-2x^2 - 6x) + (-x) \] Combining the like terms: \[ = -2x^2 - 6x - x \] \[ = -2x^2 - 7x \] Thus, the simplified form of \( (f+g)(x) \) is: \[ (f+g)(x) = -2x^2 - 7x \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium